The Oppression of Women and the Patriarchal System in Nawal El Saadawi's Novel Catatan Dari Penjara Perempuan: A Study of Radical Feminism - Nining Maida; Rohanda Rohanda; Dedi Supriadi (Gunung Djati Conference Series, 2025)
This research discusses oppression of women and the patriarchal system in Nawal el Saadawi's novel Catatan Dari Penjara Perempauan uses a radical feminism approach. The novel shows how women experience structural repression institutionalized by the state, religion, and patriarchal culture. The female characters in the novel are depicted as subjects whose bodies and minds are controlled by the system of power, but also show various forms of active resistance to this domination. Through symbolic actions, verbal expressions, and legal awareness, they dismantle oppressive power relations. This research uses a descriptive qualitative method with literature study techniques on the text of the novel as the main data source. The analysis was conducted by identifying forms of oppression and women's resistance reflected in the novel's narrative. The radical feminism approach is used because it is able to unravel the ideological roots of oppression against women, especially through control over women's bodies and expressions in a patriarchal system and authoritarian regime. The results show that this novel is not only a record of Nawal El Saadawi's personal experience, but also an ideological field of resistance to systemic patriarchal power. Thus, this study emphasizes the role of literature as a medium of social criticism and a space for struggle for gender equality.